Scary summer - Keenan, Sheila; Stine, R. L.; Stine, R. L.; Stine, R. L.; Baker, Kyle.; Haspiel, Dean.; Naifeh, Ted. (New York : Scholastic, 2007)
Graphic novel adaptations of three of R.L. Stine's Goosebumps books.
Revenge of the lawn gnomes / adapted and illustrated by Dean Haspiel -- Ghost beach / adapted and illustrated by Ted Naifeh -- The horror at Camp Jellyjam / adapted and illustrated by Kyle Baker -- Meet the artists.
"3 ghoulish Graphix tales"--Cover.
Keywords: Stine, R. L. -- Adaptations -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Ghosts -- Fiction; Graphic novels; Horror stories; Monsters -- Fiction; Graphic novels; Horror comic books, strips, etc